Cell responses and hemocompatibility of g-HA/PLA composites - Li, J.; Zheng, W.; Zheng, Y.; Lou, Xia (Springer Open, 2011)
The objective of this study was to investigate the hemocompatibility and cell responses to some novel poly(L-lactide) (PLA) composites containing surface modified hydroxyapatite particles for potential applications as a bone substitute material. The surface of hydroxyapatite (HA) particles was first grafted with L-lactic acid oligomers to form grafted HA (g-HA) particles. The g-HA particles were further blended with PLA to prepare g-HA/PLA composites. Our previous study has shown significant improvement in tensile properties of these materials due to the enhanced interfacial adhesion between the polymer matrix and HA particles. To further investigate the potential applications of these composites in bone repair and other orthopedic surgeries, a series of in vitro and in vivo experiments were conducted to examine the cell responses and hemocompatibility of the materials. In vitro experiments showed that the g-HA/PLA composites were well tolerated by the L-929 cells. Hemolysis of the composites was lower than that of pure PLA. Subcutaneous implantation demonstrated that the g-HA/PLA composites were more favorable than the control materials for soft tissue responses. The results suggested that the g-HA/PLA composites are promising and safe materials with potential applications in tissue engineering.